2001
DOI: 10.1364/ao.40.002117
|View full text |Cite
|
Sign up to set email alerts
|

Vibration-induced phase errors in high-speed phase-shifting speckle-pattern interferometry

Abstract: We present results from numerical simulations of a dynamic phase-shifting speckle interferometer used in the presence of mechanical vibrations. The simulation is based on a detailed mathematical model of the system, which is used to predict the expected frequency response of the rms measurement error, in the time-varying phase difference maps, as a result of vibration. The performance of different phase-shifting algorithms is studied over a range of vibrational frequencies. Phase-difference evaluation is perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…7 These phase profiles are shifted by arbitrary offset values for clarity and were obtained for τ r =60 with no vibration isolation and with the vacuum pump running. Τhe experimental results suggest that short M-value phase-shifting algorithms, such as the Carré and the 8-rect ones, minimise the random phase errors introduced by the vibration noise.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 These phase profiles are shifted by arbitrary offset values for clarity and were obtained for τ r =60 with no vibration isolation and with the vacuum pump running. Τhe experimental results suggest that short M-value phase-shifting algorithms, such as the Carré and the 8-rect ones, minimise the random phase errors introduced by the vibration noise.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of this high-speed speckle interferometry system in the presence of harmonic vibrations was recently analyzed using controlled experiments and numerical simulations [7]. It was demonstrated that the frequency response of the rms phase error depends mainly on the form and length of the temporal window of the phase shifting algorithm and also on the framing rate of the video camera.…”
Section: Introductionmentioning
confidence: 99%
“…[13]. The simulations represented the interference signal between a temporal phase-shifted reference beam with φ = π /2, and an object beam propagating from a surface submitted to pseudo-random vibration.…”
Section: A Pseudo-random Vibrationsmentioning
confidence: 99%
“…13,14 Long window TPS algorithms present low sensitivity to high-frequency vibration, but they are vulnerable to highamplitude low-frequency vibration. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the sensitivity of a dynamic PS interferometry system to single frequency vibration was numerically analyzed by the present authors. 10 It was shown that the rms phase error frequency response depends mainly on the length and shape of the sampling window from which the PS algorithm coefficients are evaluated, and also on the framing rate of the camera.…”
Section: Introductionmentioning
confidence: 99%